Improved professional practices in social services through Emotional Labor strategies - Gvelesiani, Tea; Sadzaglishvili, Shorena; Gigineishvili, Ketevan; Lekishvili, Ketevan; Namitcheishvili, Salome (Frontiers in Psychology, 2023)
The present study provides an analysis of Emotional Labor (EL) and its consequences for professional social work practitioners in Georgia. This mixed-methods study comprised two stages. First, a qualitative study was conducted to determine the organizational characteristics defined by social work practitioners (N = 70). Second, a quantitative study was undertaken among the members of the Georgian Association of Social Workers (N = 165) to determine the direct and indirect influences of organizational characteristics on EL and work outcomes, namely, personal accomplishment and burnout. The results are pragmatic and applicable for organizations providing social services to gain positive results at the individual and organizational levels.